Letting Down the Team? Social Effects of Team Incentives. Issue 5 (1st October 2015) - Babcock, Philip; Bedard, Kelly; Charness, Gary; Hartman, John; Royer, Heather
Abstract: This paper estimates social effects of incentivizing people in teams. In three field experiments featuring exogenous team formation and opportunities for repeated social interactions, we find large team effects that operate through social channels. In particular, assignment to a team treatment increases productivity by 9%–17% relative to an individual incentive treatment, even though the individual incentive yields a higher private return. Further, we find that in a choice treatment individuals overwhelmingly prefer the individual incentive to the team incentive, despite the latter being more effective. These results are most consistent with the team effects operating through guilt or social pressure as opposed to pure altruism.